Multi-objective design of thickness and curvature of a bendable structure considering delamination and strength characteristics. Issue 1 (14th March 2018) - Lee, Hyunseok; Chae, Han-Seok; Joo, Won-Seok; Lee, Jongsoo
Graphical abstract: Abstract: The present study explores the finite element analysis and design optimization of a multi-layered bendable structure (i.e., a device of smart watch) considering delamination characteristics and materials strength conditions. The materials used for device and rubber in the smart watch are polycarbonate and thermoplastic polyurethane, respectively. Mooney-Rivlin model is employed to accommodate the hyperelastic behavior of rubber under large deformation. An evaluation of the delamination between layers and adhesive of the smart watch is conducted based on the cohesive zone model. The present study suggests the physical definitions of the vertical gap and sliding distance to describe the debonding/delamination properties in case of a bendable structure undergoing a large deformation. In the optimal design for the glass thickness, display thickness and radius of curvature, the bi-objective formal optimization is formulated to minimize both the vertical gap and sliding distance subjected to constraints on materials strength requirements of glass stress and display stress. The optimal design solutions are obtained using 2nd order polynomial based response surface models and a non-dominated sorting genetic algorithm (NSGA-II) in the context of multi-objective approximate optimization. In the optimization result, the sliding distance is improved by 25.64% with the secured stress limits compared to an initial design. The sliding distance value has been more enhanced under the contribution of the shear mode of delamination than the vertical gap under the normal mode. The study accommodates more enhanced design solutions to minimize debonding/delamination properties under strength requirements.